(untitled) (Bangladesh Journal of Medical Science, 2015)
Xanthoma of bone is a very rare benign bone disorder with features mimicking primary bone tumours or metastatic lesions and their definitive diagnosis is very difficult. This condition can occur in patients with both normal and abnormal lipid profiles. Xanthoma of femur in a normolipidemic patient is very rare. Histopathological study gives a definitive diagnosis. We report a case of a 17 year old patient who was hospitalized in orthopedic department for fracture of the right femur with a lytic lesion at the fracture site. The patient was normolipidemic and hypothyroid. The diagnosis of xanthoma was selected histomorphologically. The fracture was treated surgically by nailing and bone graft. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.396-398